Correlation of Soil Environmental to Diversity the Entomopathogenic Fungi - Rose Novita Sari Handoko; Aminudin Afandhi; Amin Setyo Leksono (Indonesian Journal of Environment and Sustainable Development, 2017)
Ecosystem rice fields that have high diversity, able to control the pest. Habitat entomopathogenic fungi in the soil have been examined on cabbage plants but has not been reported in the rice field. The study was conducted through surveys of crops and paddy fields by the application of IPM in Kasembon Malang. A total of 5 points soil samples were determined diagonally used in this study. Isolation of entomopathogenic fungi from the rhizosphere of paddy is done by plate dilution method. Entomopathogenic fungi were identified to genus level by observing the macroscopic and microscopic characteristics. Koch's postulates done on Tenebrio molitor, then observe the symptoms and mortality of Spodoptera litura time pathogenicity test. The results showed that the genus of entomopathogenic fungi in the rhizosphere of rice is Penicillium sp., Aspergillus sp. and has not been identified. Chemical analysis of soil for pH is 4.00 to 5.00. Soil organic matter is 1.89% to 3.20%. Keywords: diversity, entomopathogenic fungi, integrated pest management, rhizosphere